Transcriptome Analysis Reveals Hub Genes Regulating Autophagy in Patients With Severe COVID-19 - Huang, Jinfeng; Wang, Yimeng; Zha, Yawen; Zeng, Xin; Li, Wenxing; Zhou, Meijuan (Frontiers in Genetics, 2022)
Background: The COVID-19 pandemic has currently developed into a worldwide threat to humankind. Importantly, patients with severe COVID-19 are thought believed to have a a higher mortality risk thancompared to those with mild conditions. However, despite the urgent need to develop new and novel therapeutic strategies, the biological features and pathogenic mechanisms of severe COVID-19 are poorly understood. Methods: Peripheral Here, peripheral blood mononuclear cells (PBMCs) from 4 four patients with severe COVID-19, 4 four patients with mild COVID-19, and 4 four healthy controls were examined by RNA sequencing (RNA-Seq) analysis. We conducted gene expression analysis and Venn diagrams to detect the specific differentially expressed genes (DEGs) in patients with severe disease compared to with those with mild conditions. Gene Ontology (GO) biological process enrichment analysis was performed to identify the significant biological processes, and protein-–protein interaction networks were constructed to extract the hub genes. These hub genes were then subjected to regulatory signatures and protein-chemical interactions interaction analysis for certain regulatory checkpoints and identification of potent chemical agents. Finally, to demonstrate the cell type-specific expression of these genes, we performed single-cell RNA-Seq analyses from using an online platform. Results: A total of 144 DEGs were specifically expressed for in severe COVID-19, and biological process GO enrichment analysis revealed a significant association of these specific DEGs with autophagy. Hub genes such as MVB12A, CHMP6, STAM, and VPS37B were then found to be most significantly involved in the biological processes of autophagy at the transcriptome level. In addition, six transcription factors, including SRF, YY1, CREB1, PPARG, NFIC, and GATA2, as well as miRNAs, namely hsa-mir-1-3p, and potent chemical agents such as copper sulfate and cobalt chloride, may cooperate in regulating the autophagy hub genes. And the Further, classical monocytes may play a central role in severe COVID-19. Conclusions: We suggest that autophagy plays a crucial role in severe COVID-19. , and Tthis study might facilitate a more profounddeeper knowledge of its the biological characteristics and progression of COVID-19 to it and, as well as the development of novel therapeutic approaches to achieve a breakthrough in the current COVID-19 pandemic.